Insurability of cryptocurrency wallets - Manikowski, Piotr; Szymczak-Łączna, Weronika; Srbinoski, Bojan (Research Papers in Economics and Finance, 2024)
This article concerns the possibilities of insuring cryptocurrency wallets using various assumptions and characteristics of perfectly insurable risk. The main goal of this article is to examine if and how cryptocurrency wallets risk fulfils the requirements of an ideally insurable risk. The topic of the research is important looking at the newest trends in financial markets and the growing number of cryptocurrency investors. The paper presents authors’ innovative method of approaching a part of cryptocurrency risk to insurance industry. Authors analysed requirements of an insurable risk and applied these requirements to a specific risk, i.e. the cryptocurrency wallet risk to further check if it is possible to insure such a risk. By introducing and defining cryptocurrency wallet risk, we found an element of cryptocurrencies which shows traits of a non-speculative risk and possibly fulfils insurability characteristics.